Promoting Passion-Based Learning as a Solution of Improving Creativity in English Classroom - Bulqia Mas’ud; Achmad Taqlidul Chair Fachruddin; Syamsinar Syamsinar (Institut Agama Islam Negeri Parepare, 2019)
This article investigates a pedagogical interference in promoting creativity in English classroom that describe the importance of creativity in learning process. The article explores the idea of passion-based learning in improving creativity in the classroom specially in English subject. By using secondary data both from journals, books, and internet sites, researcher is able to apply descriptive analysis through literary review methods. Promoting passion-based learning might be a possible way to improve creativity in English Classroom. Passion-based learning could be a solution that give ownership and authority to students to explore their own creativity in the classroom hence give them meaningful learning. Some tangible ways in this article could be applied by English teachers to create passion-based learning in English classroom that can improve the students’ reading, listening, speaking and writing skill and creativity. The emerging challenge found in this study is passion-based learning is difficult to apply in large class since it gives freedom to students choose what they want to learn hence classroom activities will not be feasible to control. Besides, passion- based learning needs creative and skilful teachers to come up with various and interesting ideas to stimulate dynamic in classroom. Therefore, the quality of teacher is highly considered in applying passion-based learning. Teachers should be expert in subjects they teach. Promoting teacher professional development need to be considered to improve creativity in English classroom with given English teachers’ opportunities to explore their potentials.